PENGARUH HIGH PERFORMANCE WORK PRACTICES TERHADAP TURNOVER INTENSIONS KARYAWAN PRODUKSI CV.CIPTA KARYA MANDIRI KOTA MOJOKERTO - RUSMAYA D, MASITA (Universitas Katolik Widya Mandala Surabaya, 2012)
The purpose of this study was to determine the influence of high performance work practices (salary of Job Satisfaction, Job Enrichment on Job Satisfaction and Employee Commitment and Job Stability of employee commitment) on employee commitment, job satisfaction and employee commitment to the turnover intensions on Independent Work CV.Cipta Karya Mandiri in Mojokerto city . The number of samples in this study is 180 samples. Data analysis technique used is Structural Equation Model (SEM) with LISREL 8.70 program. These results indicate that the salary has a positive effect on job satisfaction, job enrichment positive influence on job satisfaction and employee commitment, job stability has a positive effect on employee commitment, employee commitment negatively affect the turnover intensions, job satisfaction and turnover intensions positively mediated by employee commitmen.